Technoeconomic Evaluation of Cooperative Relaying Transmission Techniques in OFDM Cellular Networks. (19th December 2010) - Moral Moral, Antolín Antolín; Vidal Vidal, Josep Josep; Pérez Pérez, Jorge Jorge; Agustín Agustín, Adrián Adrián; Marina Marina, Ninoslav Ninoslav; Høst-Madsen Høst-Madsen, Anders Anders
Abstract : We evaluate the costs in the deployment of a 4G relay-assisted network in the 2.6 GHz band following a technoeconomic methodology that departs from cell dimensioning based on spectral efficiency and outage capacity requirements. Different decode-and-forward relaying protocols are considered in the analysis, assuming a certain traffic load evolution over a period of ten years, different geotypes, and a progressive deployment of base stations and relay stations. Results show significant benefits for operators as well as reduction in the total radiated power.